Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/joa.12979
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular structures of the ligament of the head of femur

Abstract: The ligament of the head of femur (LHF), or ligamentum teres, is believed to provide blood supply to the head of femur and mechanical stability to the hip joint. But these functions in the adult are often debated. The existence and distribution of neurovascular structures within the ligament are not widely documented. This study examined the blood vessels and nervous tissue within the LHF to determine whether the ligament may have a vascular and proprioceptive function at the hip joint. Histological sections f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Blood vessel density was calculated as a percentage of the area of the ROI that was occupied by blood vessels for each section (Perumal et al, 2019). The median and interquartile range (IQR) of blood vessel density were calculated for all samples combined, and for specific areas of each bursa.…”
Section: Discussionmentioning
confidence: 99%
“…Blood vessel density was calculated as a percentage of the area of the ROI that was occupied by blood vessels for each section (Perumal et al, 2019). The median and interquartile range (IQR) of blood vessel density were calculated for all samples combined, and for specific areas of each bursa.…”
Section: Discussionmentioning
confidence: 99%
“…The presence and integrity of central concave vessels in the round ligament of the femoral head were observed in 61% of the 266 patients in the Barrington et al [30] study. Perumal et al [31] also found a high distribution of vessels in the central concave round ligament of the femoral head as well as the presence of nerves and neuroreceptors, which suggests that the round ligament is involved in the perception of pain and proprioception. Therefore, our team believes that the destruction of the round ligament during rotational osteotomy of the femoral neck using surgical dislocation techniques may cause the following three problems: 1. loss of hip stability, leading to secondary femoral head collapse or even osteoarthritis; 2. destruction of hip proprioception; and 3. destruction of the blood supply to the femoral head concavity.…”
Section: Discussionmentioning
confidence: 96%
“…Stained slices were analyzed in transmission and polarization mode, using 20×, 40×, 200×, and 400× magnification. HE staining was used for the qualitative determination of the structure and composition of collagen (Costa et al, 2018; Perumal et al, 2019; Zhang et al, 2018), EvG staining for the occurrence and semiquantitative distribution of elastic fibers (Chan et al, 2007; Sawatsubashi et al, 2010; Sencimen et al, 2009). The anisotropic arrangement of collagen fibers was classified into four types by using polarization microscopy: densely packed parallel, mixed tight and loose parallel, densely interlaced, and mixed tight and loose interlaced (Rein et al, 2015; Rein et al, 2020; Semisch et al, 2016).…”
Section: Methodsmentioning
confidence: 99%